Human motion correction and representation method from motion camera. Issue 7 (28th July 2017) - Zhang, Hong‐Bo; Guo, Feng; Zhang, Miaohui; Lin, Ying; Hsiao, Tsung‐Chih
Abstract : Motion estimation is a basic issue for many computer vision tasks, such as human–computer interaction, motion objection detection and intelligent robot. In many practical scenes, the object movement goes with camera motion. Generally, motion descriptors directly based on optical flow are inaccurate and have low discrimination power. To this end, a novel motion correction method is proposed and a novel motion feature descriptor called the motion difference histogram (MDH) for recognising human action is proposed in this study. Motion estimation results are corrected by background motion estimation and MDH encodes the motion difference between the background and the objects. Experimental results on video shot with camera motion show that the proposed motion correction method is effective and the recognition accuracy of MDH is better than that of the state‐of‐the‐art motion descriptor.